Healing wounds: how the International Research Centers of the CGIAR help rebuild agriculture in countries affected by conflicts and natural disasters - Varma, Surendra; Winslow, Mark (Consultative Group on International Agricultural Research, 2005)
This study first reviews current thinking on the underlying causes of conflicts and disasters, identifying poverty as a major driver of both. Poverty breeds frustration, compelling the poor to turn to violence. Most of the poor are involved in rural agriculture, so pro-poor investments in agricultural development can alleviate poverty and thereby reduce the possibilities of conflict and also contribute to natural disaster preparedness. History shows that agricultural research is a particularly high-payoff leverage point for stimulating economic growth and poverty reduction. Based on case studies from 12 CGIAR Centers, the study then describes major Center contributions and lessons learned in five prominent areas:; Alleviating hunger by rebuilding seed and food systems;; Safeguarding and restoring agrobiodiversity;; Rebuilding human and institutional capacities;; Reducing future vulnerability to these crises; and; Making relief aid more effective and efficient.; It highlights how the Centers’ work addresses the root causes of conflicts and disasters, in addition to providing immediate relief by working together with a diverse group of partners, including donors and relief and development agencies, and by building bridges between the various partners for implementing long-term work plans